Influence of Work Discipline, Financial Compensation, and Work Environment on Employee Performance at PT. Works of Eternal Dewata - DEWI, Vidya Adisstya; SURIANI, Ni Nyoman; WIDARI, Dewa Ayu Putu Niti (PT Batara Swastika Harati, 2024)
This research examines and analyzes the influence of work discipline, financial compensation, and the work environment on employee performance. This research was conducted at PT. Karya Dewata Abadi with a research sample of 53 respondents taken using saturated sampling techniques. All data obtained from the questionnaire distribution is suitable for use and is then analyzed using multiple linear regression and hypothesis testing (t-test and f-test). The research results show that (1) Work discipline, financial compensation and work environment positively and significantly affect employee performance at PT. Karya Dewata Abadi (2) Work discipline positively and significantly affects employee performance at PT. Karya Dewata Abadi. It means that the more work discipline increases, the more employee performance at PT. Karya Dewata Abadi will increase. (3) Financial compensation positively and significantly affects employee performance at PT. Karya Dewata Abadi. It means that the greater the financial compensation, the greater the employee performance at PT. Karya Dewata Abadi. (4) The work environment positively and significantly affects employee performance at PT. Karya Dewata Abadi. It means that the better the work environment is, the greater the employee performance at PT. Karya Dewata Abadi.